Description of attitudes about professional ethics in students of two professional schools of health, 2016 - Salazar, Emma (2019)
Introduction: The university has the responsibility to train integral professionals, who are ethically committed in their professional actions. Objective: To compare the attitudes about professional ethics in students of two schools of health area from the Universidad Nacional Mayor de San Marcos. Methods: A transversal study. 284 undergraduate students participated in the study and a validate version of Hirsch Professional Ethics Attitude Scale was applied to them. Four competences from Hirch’s scale were evaluated: cognitive and technical, social, ethical and affective-emotional. Results: The assessment of the answers was similar in both schools, with positive ones greater than 80% in three competitions. Conclusion: A higher percentage of positive attitude was found in the four competences. Both groups valuing in first place, the affective-emotional component; in second place, cognitive and technical component; thirdly, ethics and finally, the social component.